Enhancing Stakeholder Participation in Urban Mobility Planning: the NISTO Evaluation Framework. - Keseru, Imre; Bulckaen, Jeroen; Macharis, Cathy (My University, 2015)
Public participation and stakeholder involvement have become core prerequisites of a comprehensive and fair transport planning process. In this paper, we show how the multi-actor multi-criteria analysis (MAMCA) methodology can enhance urban and regional mobility planning and decision-making by considering conflicting stakeholder objectives and helping to identify synergies and disagreement between different stakeholder groups. We suggest the application of MAMCA as part of the NISTO evaluation framework that offers tools to appraise small-scale mobility projects through a toolkit of multi-criteria analysis, MAMCA and target monitoring. MAMCA provides a tool to appraise the preferences of the stakeholders involved or affected by a project. It is based on assessing the evaluation criteria of the different stakeholder groups rather than appraising the project based on a set of common criteria agreed on with all stakeholders at the beginning of the process. Therefore the evaluation shows which implementation alternatives or scenarios each group would prefer and allows for a straightforward comparison of preferences across all stakeholder groups. The application of the MAMCA is demonstrated through the initial results of the evaluation of five demonstration projects in North-West Europe. We show that MAMCA is suitable for a range of mobility projects since it can handle the diversity of stakeholder groups and their objectives. In addition it offers the practitioner a well-structured way of carrying out the whole evaluation process. The application of MAMCA also has the added value of broadening the evaluation process to a wide range of stakeholders instead of limiting it to experts. As opposed to previous approaches, the MAMCA methodology aims to provide a balanced evaluation process where the stakeholders have equal weight, i.e. no priority is given to decision makers, users groups or experts. Our analysis of the process of the identification of stakeholders and their objectives also suggests that there is no generic recipe for the range of stakeholders to be involved in different projects, their objectives and the data that needs to be collected for the evaluation. The MAMCA methodology will be offered to practitioners as a simple-to-use web-based software tool that can collect stakeholder objectives and weights, as well as the input of experts and monitoring data for the evaluation of the alternatives and display the outcome on graphs. Therefore we hope that the tool will improve participation in urban decisionmaking and evaluation thorough the better integration of diverse stakeholder preferences.
Keywords: Methode; Stadtplanung; Raumplanung; Planungsprozess; Partizipation; Mobilitätsplanung; Evaluation